A vontade livre em Nietzsche - Ana Marta Lobosque de Oliveira (2010)
The thesis contends that Nietzsche, on the one hand, severely criticizes the doctrine of freedom of will in the philosophical tradition, and, on the other hand, presents his own conception of free will. In light of the broader context of the criticism to the actual will and of the genealogical investigation of moral made by this philosopher, we will examine the passages of his work which specifically criticize this concept, whilemaking reference to some authors during the course of the history of philosophy, namely, Plato, Aristotle, Saint Augustine, Kant and Schopenhauer. Next, we will investigate to what extent Nietzsche questions and promotes the possibility of giving a new meaning to free will.